Dynamic modelling of information systems - Sol, H. G. 1951-; Hee, Kees Max van 1946- (North-Holland, 1991)
The use of dynamic models in the development of information systems is regarded by many researchers as a promising issue in design support. Modelling the dynamics of information systems is likely to improve the quality and the performance of the design products. Dynamic modelling as a new approach for dynamic analysis of problems within an existing situation, and design and evaluation of different solution strategies may overcome many difficulties in the design process
"... International Working Conference on 'Dynamic Modelling of Information Systems', April 9-10, 1990, Noordwijkerhout, the Netherlands"--Pref
Includes bibliographical references
Keywords: COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Information storage and retrieval systems; System design; Informatik; System design -- Congresses; Information storage and retrieval systems -- Congresses; Informationssystem; Dynamische Modellierung; Dynamisches Modell; Noordwijkerhout; Konferenzschrift